PHYTOPLANKTON OF BOZTEPE RECAI KUTAN DAM LAKE LOCATED IN UPPER EUPHRATES RIVER BASIN (EASTERN ANATOLIA) - Sonmez, Feray; Alpaslan, Kenan; Karakaya, Gokhan; Sen, Bulent (Parlar Scientific Publications (P S P), 2019)
Seasonal changes in phytoplankton community of Bortepe Recai Kutan Dam Lake were investigated on samples taken from three stations between January 2014 and December 2014. The phytoplankton of Bortepe Recai Kutan Dam Lake consisted of 20 taxa belonging to Bacillariophyta (12 taxa), Chlorophyta (1 taxa), Chrysophyta (1 taxon), Cyanobacteria (2 taxa), Dinozoa (2 taxa) and Euglenozoa (2 taxa). Members of Bacillariophyta was commonly observed in January and August whilst Chlorophyta grew well in September. Chrysophyta only occurred and recorded in high numbers in September. Cyanobacteria became dominant in spring, at the end of summer and also in autumn. However, Dinozoa was remarkably conspicuous in spring and fall as well as in winter in terms of prevalence. Excessive growth of Cyanobacteria, which is a characteristic aspect of mesotrophic lakes, was observed in lake in both April and August. Euglenozoa also occurred at the end of summer and early autumn. Phytoplankton composition was appeared to be affected mainly by temperature, phosphate and nitrate. Secchi disk depth, concentrations of plant nutrients (TN, TP), chlorophyll-a analyzed in the present study supported the view that the Bortepe Recai Kutan Dam Lake could be included in mesotrophic lake category.
Keywords: Phytoplankton; nutrient; Bortepe Recai Kutan Dam Lake; Malatya; Turkey